2012
DOI: 10.1103/physrevlett.109.097402
|View full text |Cite
|
Sign up to set email alerts
|

Fano Resonances in the Midinfrared Spectra of Single-Walled Carbon Nanotubes

Abstract: This work revisits the physics giving rise to the carbon nanotube phonon bands in the midinfrared. Our measurements of doped and undoped samples of single-walled carbon nanotubes in Fourier transform infrared spectroscopy show that the phonon bands exhibit an asymmetric line shape and that their effective cross section is enhanced upon doping. We relate these observations to electron-phonon coupling or, more specifically, to a Fano resonance phenomenon. We note that the dopant-induced intraband (not interband)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“…In addition to plexcitons, these plasmon resonances in strips of aligned SWCNTs can strongly couple with other quasi-particles, such as phonons. Falk et al showed strong coupling between longitudinal optical phonons in SiO 2 substrates (attenuation peak ν 1 in figure 14 a ), infrared-active E 1 and E 1 u phonons in CNTs [112,113] (attenuation peak ν 2 in figure 14 a ) and plasmon resonances (attenuation peak ν 3 in figure 14 a ), by putting patterned strips with various L of aligned SWCNT films on SiO 2 substrates. The strong coupling enhances usually weak infrared-active phonons and leads to an asymmetric lineshape, which can be fit very well with a Fano resonance formula [111], as shown in figure 14 b .…”
Section: Plasmon Resonances and Hybridization In Patterned Aligned Simentioning
confidence: 99%
“…In addition to plexcitons, these plasmon resonances in strips of aligned SWCNTs can strongly couple with other quasi-particles, such as phonons. Falk et al showed strong coupling between longitudinal optical phonons in SiO 2 substrates (attenuation peak ν 1 in figure 14 a ), infrared-active E 1 and E 1 u phonons in CNTs [112,113] (attenuation peak ν 2 in figure 14 a ) and plasmon resonances (attenuation peak ν 3 in figure 14 a ), by putting patterned strips with various L of aligned SWCNT films on SiO 2 substrates. The strong coupling enhances usually weak infrared-active phonons and leads to an asymmetric lineshape, which can be fit very well with a Fano resonance formula [111], as shown in figure 14 b .…”
Section: Plasmon Resonances and Hybridization In Patterned Aligned Simentioning
confidence: 99%
“…By comparing the nanotubes' spectra to spectra of graphene nanoribbons on SiO2, we identify ν3 with the 1168 cm -1 the longitudinal optical (LO) phonon in the SiO2 substrate [16,20]. The ν2 resonance at 1590 cm -1 corresponds to the infrared-active E1 and E1u phonon modes [21,22] of carbon nanotubes. These phonon modes, though closely related to the strong G-band Raman modes of nanotubes [23], are ordinarily very weak spectroscopic features.…”
Section: Main Textmentioning
confidence: 99%
“…[ 22 ] propose that this effect can be due to the Fano resonance of diamond Raman mode and some continuum of modes connected to the conductive states on the nanodiamond surface. It seems that this behavior is not limited to diamond as similar Fano resonances at the phonon frequency were observed in doped single-walled carbon nanotubes [ 43 ].…”
Section: Discussionmentioning
confidence: 67%